Professoras de creche e suas identidades: trajetórias narradas com a linguagem matemática em um grupo de estudos - Sala, Elaine Cristina Florencio (2024)
This master's thesis, linked to the Professional Postgraduate Program in Education (PPGPE) at the Federal University of São Carlos (UFSCar), describes results and directions of an investigation that aimed to analyze the professional identity of Early Childhood Education teachers and the constitution of their practices, in relation to Mathematics, with babies and very young children, when participating in a study group. The research, of a qualitative nature, is based on the field of teaching narratives with the method of the German sociologist Fritz Schütze, which places as a base assumption the organization of data produced from the following steps: 1. Formal analysis of the text; 2. Structural description of the content; 3. Analytical abstraction; 4. Analysis of knowledge; 5. Contrastive comparison; and 6. Construction of a theoretical model. The theme highlights the work with mathematical language from zero to three years old by highlighting the construction of identity and the trajectories narrated by teachers, in a movement of continued training, in Early Childhood Education when they are part of the Study and Research Group "Other Views on Mathematics" (GEOOM/UFSCar). A possible contribution, in view of the conclusion, was the possibility of knowing, in more detail, who the daycare teachers are who participate in GEOOM/UFSCar, revealing their life paths, training, tensions and teaching when they reflected on the real pedagogical experience, given the few studies with mathematical language in the space-time of daycare centers.